Ritmo de atividade vocal de machos de Baleia Jubarte (Megaptera novaeangliae) - Casagrande, Thamires (Brasil, 2016)
Many studies of vocal activity of humpback whales have focused on investigating the temporal and geographical pattern changes in the male song. This knowledge can contribute to the species management, explaining how the behavioral traits are modulated by external factors of the environment in which the individual is inserted. This knowledge associated with information about the life history, biology and ecology of the species, provides the development of more successful conservation measures. Determining the existence of a periodic pattern of vocal activity of male humpback whales along the breeding season may support the hypothesis of endogenous biological rhythms, or how the biotic or abiotic zeitgebers could modulate the expression of the vocal behavior of these animals, which is so important for their reproductive success and maintainance of a increasing and healthy population. The aim of this study was to verify the existence of such rhythm in the occurrence of male vocal displays in the vicinity of the National Marine Park of Abrolhos. For this, we used acoustic data previously collected during the years 2003, 2004 and 2005. In 2005 the effort was divided into two areas, a treatment area where whale watching boat traffic is frequent similar located in the same general area to the previous years and a control area with rare boat traffic. The recordings were visually and aurally inspected every 2 minutes using XBAT an application that runs in MATLAB. These 2-minute samples were categorized as: presence or absence of humpback vocal activity and also vessel noise. Spectral analyzes were performed using Cosinor and a correlation test through a routine developed in MATLAB. Our results show the existence of a vocal activity pattern for all years in the treatment area, but not in the control area. Vocal activity concentrated between 15:00 pm and 10:00 am. The same pattern was not observed in all months of 2005 in the control area where the boat traffic is reduced. Coincidentally, the temporal pattern of vessel ...